2012
DOI: 10.1103/physrevlett.108.036801
|View full text |Cite
|
Sign up to set email alerts
|

Gating the Charge State of Single Molecules by Local Electric Fields

Abstract: The electron acceptor molecule TCNQ is found in either of two distinct integer charge states when embedded into a monolayer of a charge transfer-complex on a gold surface. Scanning tunneling spectroscopy measurements identify these states through the presence/absence of a zero-bias Kondo resonance. Increasing the (tip-induced) electric field allows us to reversibly induce the oxidation/reduction of TCNQ species from their anionic or neutral ground state, respectively. We show that the different ground states a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
106
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(120 citation statements)
references
References 29 publications
13
106
0
1
Order By: Relevance
“…1(b)). From these and other characteristic observations being analogous to several previous works, [70][71][72][73][74][75] it could be concluded that the molecules are charged in the field of the scanning-probe junction. It was concluded further that without applied bias a localized state of the molecule was close enough to the substrate's Fermi level, such that at a given threshold electric field the localized state can be shifted across the Fermi level of the substrate, which will change the (average) occupation of the state and hence the charge state.…”
Section: Summing Up Previous Worksupporting
confidence: 66%
“…1(b)). From these and other characteristic observations being analogous to several previous works, [70][71][72][73][74][75] it could be concluded that the molecules are charged in the field of the scanning-probe junction. It was concluded further that without applied bias a localized state of the molecule was close enough to the substrate's Fermi level, such that at a given threshold electric field the localized state can be shifted across the Fermi level of the substrate, which will change the (average) occupation of the state and hence the charge state.…”
Section: Summing Up Previous Worksupporting
confidence: 66%
“…1-4 Control over the charge state of atoms and molecules on surfaces have been achieved experimentally [2][3][4][5][6][7][8][9] and examined theoretically. [10][11] For example, the charging/discharging of nanoparticles on substrates for use as efficient nanoscale memory devices, [12][13] selective adsorption of CO and NH 3 by mass-selected molybdenum sulfide cations on gold surfaces 14 as well as the improved catalytic activity towards the oxidation of adsorbed CO molecules by partially charged gold clusters on metal oxide supports, 1, 15 illustrate the wide range of possibilities.…”
Section: Introductionmentioning
confidence: 99%
“…In the experiment, the electronic levels of the QD are gated with respect to the Fermi level E F of the tip by applying a bias voltage to the tip-surface junction [ Fig. 1 [6][7][8][9][10]. In this way, the charge state of the QD can be changed, e.g., if the bias voltage V applied to the junction reaches a critical value V − that aligns one of the QD's occupied electronic levels with E F , this level is depopulated [ Fig.…”
mentioning
confidence: 99%